2021
DOI: 10.1371/journal.pone.0248495
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting youths’ practice of preventive measures toward the outbreak of COVID-19 in Oromia special zone surrounding Finfinnee, Ethiopia

Abstract: Background Coronavirus disease 2019 (COVID-19) is a highly contagious viral infection, and it has negative effects on public health. The practice of preventive measures of the disease supports containment processes of the spread of coronavirus. However, the practice of preventive measures is affected by several associated risk factors. Objective This study aimed to investigate the associated factors that limit the youths’ practice of preventive measures against COVID-19 in the study area. Methods A communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
4
20
1
Order By: Relevance
“…In another way, a difference in sample size affects the result of a study in which the larger sample size results in a more accurate determination of findings. The finding of this study is higher as compared with a study conducted at Oromia Special zone surrounding Finfinee [31] and on adult populations of Sidama regional state [27] in which 31.0% and 24.4% of the respondents adhered to COVID-19 prevention measures respectively. This may be due to a difference in source population in which students may be more likely to apply COVID-19 prevention measures as schools commenced rules and regulations regarding COVID-19.…”
Section: Plos Onecontrasting
confidence: 81%
“…In another way, a difference in sample size affects the result of a study in which the larger sample size results in a more accurate determination of findings. The finding of this study is higher as compared with a study conducted at Oromia Special zone surrounding Finfinee [31] and on adult populations of Sidama regional state [27] in which 31.0% and 24.4% of the respondents adhered to COVID-19 prevention measures respectively. This may be due to a difference in source population in which students may be more likely to apply COVID-19 prevention measures as schools commenced rules and regulations regarding COVID-19.…”
Section: Plos Onecontrasting
confidence: 81%
“…From our study, almost all young adults claimed that they took at least one action to control the spread of COVID-19 including hand washing and wearing face masks, but fewer young adults reported avoiding hand shaking, social distancing, avoiding groups of more than 4 people, avoiding touching eyes, nose and mouth, and sneezing inside the elbow. This finding is consistent with other studies which found that relatively fewer young adults practiced physical distancing (Feyisa, 2021;Varol et al, 2021;Babalola et al, 2020). These findings point to the need to strengthen health education interventions including working with youth champions to promote personal responsibility in the uptake of the recommended preventive measures.…”
Section: Discussionsupporting
confidence: 92%
“…Coronavirus disease 2019 (COVID-19) is an infectious and transmissible disease that spreads primarily through droplets of saliva or discharge from the nose when an infected person coughs or sneezes (WHO, 2021;Shereen, Khan, Kazmi, Bashir, & Siddique, 2020). COVID-19 was declared a global pandemic by the World Health Organization (WHO) on March 11, 2020, and Uganda declared its first case on March 21, 2020 (Feyisa 2021;WHO 2020;Orgilés, Morales, Delvecchio, Mazzeschi, & Espada, 2020;Oosterhoff, Palmer, Wilson, & Shook, 2020). The WHO declaration brought with it global panic, fear of contracting the disease, and the disruption of social life.…”
Section: Introductionmentioning
confidence: 99%
“…Younger people who are male, less educated, have lower income, who pay less attention or knew very little about COVID-19 were more likely to take proactive measures against COVID-19 infection [ 45 ]. Young people are also more likely to have asymptomatic or develop mild, transient illness making it possible to ignore the symptoms as it may not disturb their routine lives [ 46 ]. This study finding therefore aligns with prior observations.…”
Section: Discussionmentioning
confidence: 99%